2003
DOI: 10.1038/sj.bjc.6600666
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism of resistance to TRAIL/Apo2L-induced apoptosis of newly established glioma cell line and sensitisation to TRAIL by genotoxic agents

Abstract: Most tumour cells are sensitive to TRAIL-induced apoptosis, but not normal cells; thus, cancer therapy using TRAIL is expected clinically. Several tumour cells are resistant to TRAIL-induced apoptosis, and various mechanisms of such resistance were reported in individual cases. In this study, we established a TRAIL-resistant glioma cell line, which completely lacked TRAIL receptors. In addition, this tumour cell line had wild-type p53 tumour-suppressive gene, suggesting new mechanisms for tumour cells to expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 30 publications
2
29
3
Order By: Relevance
“…Cisplatin treatment, in contrast to previously reported findings in other cultured cancer cells (27,29), did not significantly alter the phenotypic expression of the TRAIL functional receptors DR4/DR5 or the decoy receptors DcR1/DcR2 (Fig. 5A).…”
Section: Sensitivity Of Esophageal Cancer Cells To Apo2l/ Trailcontrasting
confidence: 96%
See 1 more Smart Citation
“…Cisplatin treatment, in contrast to previously reported findings in other cultured cancer cells (27,29), did not significantly alter the phenotypic expression of the TRAIL functional receptors DR4/DR5 or the decoy receptors DcR1/DcR2 (Fig. 5A).…”
Section: Sensitivity Of Esophageal Cancer Cells To Apo2l/ Trailcontrasting
confidence: 96%
“…2B and 9A). Previous studies have indicated that cytotoxic chemotherapeutic drugs sensitize cultured cancer cells to TRAIL by up-regulation of the receptors DR4/ DR5 (25,27,29,40), enhanced DISC formation/function (26,41,42), or alterations of the phenotypic expression of proapoptotic/antiapoptotic proteins (25,34,43,44) that is paralleled with an overall increase of caspase-8 activation and massive cell death. Our data did not indicate a significant alteration of TRAIL receptor expression in CDDP-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some resistant glioma cell lines could be sensitised by the treatment with the translation inhibitor cycloheximide, implicating a labile inhibitor of TRAIL signalling in the resistance of those cell lines (Rieger et al, 1998;Wu et al, 2000;Hao et al, 2001;Rohn et al, 2001;Fulda et al, 2002a). Lack of surface expression of TRAIL death receptors was reported in one glioma cell line (Arizono et al, 2003). Co-treatment of some resistant lines with chemotherapy drugs, which raised TRAIL receptor levels, enhanced TRAIL sensitivity (Nagane et al, 2000;Rohn et al, 2001;Shinohara et al, 2001;Arizono et al, 2003).…”
mentioning
confidence: 99%
“…As cancer therapy in the clinic often involves the use of multiple therapeutic regimens, it was of interest to determine if HGS-ETR1 in combination with commonly used anticancer agents could enhance HGS-ETR1 activity in vitro and in vivo. Previous studies have shown that chemotherapeutic agents enhance TRAIL-induced cell killing of various tumour cells in vitro and in vivo (Naka et al, 2002;Arizono et al, 2003;Ray and Almasan, 2003;Singh et al, 2003). Combination treatment with chemotherapeutic agents in vitro also enhance murine TRAIL-R1 and TRAIL-R2 agonistic antibody-induced cell killing (Ohtsuka et al, 2003), and combination of a murine TRAIL-R2 antibody with adriamycin or paclitaxel showed greater inhibition of tumour growth compared to antibody alone in a breast cancer model in vivo .…”
Section: Discussionmentioning
confidence: 99%